2013
DOI: 10.3109/10428194.2013.821703
|View full text |Cite
|
Sign up to set email alerts
|

New onset pancytopenia in adults: a review of underlying pathologies and their associated clinical and laboratory findings

Abstract: Pancytopenia is regularly encountered in hematology practice, yet there exist few published assessments of the frequencies of various etiologies, and these frequencies exhibit substantial geographic variation. We reviewed bone marrow specimens from pancytopenic adults to determine the most common etiologies and to identify associations with clinical and laboratory findings. Of 132 patients with no history of hematolymphoid neoplasia, no prior bone marrow study for pancytopenia and no recent cytotoxic chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Toxic changes and degenerative changes were observed in the granulocytes of these patients, which may be a significant reason for the false-positive results in the automated measurement. Blood counts and peripheral smear findings may provide insight into the likelihood of a clonal etiology (7).…”
Section: Discussionmentioning
confidence: 99%
“…Toxic changes and degenerative changes were observed in the granulocytes of these patients, which may be a significant reason for the false-positive results in the automated measurement. Blood counts and peripheral smear findings may provide insight into the likelihood of a clonal etiology (7).…”
Section: Discussionmentioning
confidence: 99%
“…This means that bicytopenia is as important as pancytopenia being associated with clonal disorders (commonly, lymphoid neoplasms) in about one third of cases. In Western studies, nearly two thirds of adult cases with new onset pancytopenia had a clonal etiology; however, myeloid neoplasms were the most common (Imbert et al 1989;Devitt et al 2014). Hypersplenism was seen in 27 % of pancytopenia patients and 18 % of bicytopenia patients.…”
Section: Discussionmentioning
confidence: 96%
“…A wide variety of disorders can cause pancytopenia; however, the frequency with which each condition is associated with pancytopenia differs according to geographical distribution and genetic differences (Devitt et al 2014). In the present study, the most common cause of pancytopenia was found to be clonal hematopoietic disorders (34 %), followed by hypersplenism (27 %) and then aplastic anemia (21 %).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations